Translating advances in reading comprehension research to educational practice - Danielle S. McNAMARA; Panayiota KENDEOU (International Electronic Journal of Elementary Education, 2011)
The authors review five major findings in reading comprehension and their implications for educational practice. First, research suggests that comprehension skills are separable from decodingprocesses and important at early ages, suggesting that comprehension skills should be targeted early, even before the child learns to read. Second, there is an important distinction between readingprocesses and products, as well as their causal relationship: processes lead to certain products. Hence, instructional approaches and strategies focusing on processes are needed to improve students’reading performance (i.e., product). Third, inferences are a crucial component of skilled comprehension. Hence, children need scaffolding and remediation to learn to generate inferences, even when they know little about the text topic. Fourth, comprehension depends on a complex interaction between the reader, the characteristics of the text, and the instructional task, highlighting the need for careful selection of instructional materials for individual students and specific groups of students. Finally, educators may benefit from heightened awareness of the limitations and inadequacies of standardized reading comprehension assessments, as well as the multidimensionality of comprehension to better understand their students’ particular strengths and weaknesses.